Causal relationship between gut microbiota and diabetic nephropathy: a two-sample Mendelian randomization study - Yan, Shuxiang; Wang, Hua; Feng, Baiyu; Ye, Lin; Chen, Anqun (Frontiers in Immunology, 2024)
Objective: Emerging evidence has provided compelling evidence linking gut microbiota (GM) and diabetic nephropathy (DN) via the "gut-kidney" axis. But the causal relationship between them hasn't been clarified yet. We perform a Two-Sample Mendelian randomization (MR) analysis to reveal the causal connection with GM and the development of DN, type 1 diabetes nephropathy (T1DN), type 2 diabetes nephropathy (T2DN), type 1 diabetes mellitus (T1DM), and type 2 diabetes mellitus (T2DM).We used summary data from MiBioGen on 211 GM taxa in 18340 participants. Generalized MR analysis methods were conducted to estimate their causality on risk of DN, T1DN, T2DN, T1DM and T2DM from FinnGen. To ensure the reliability of the findings, a comprehensive set of sensitivity analyses were conducted to confirm the resilience and consistency of the results.Results: It was showed that Class Verrucomicrobiae [odds ratio (OR) =1.5651,